A novel dropout mechanism with label extension schema toward text emotion classification. Issue 2 (March 2023) - Li, Zongxi; Li, Xianming; Xie, Haoran; Wang, Fu Lee; Leng, Mingming; Li, Qing; Tao, Xiaohui
Abstract: Researchers have been aware that emotion is not one-hot encoded in emotion-relevant classification tasks, and multiple emotions can coexist in a given sentence. Recently, several works have focused on leveraging a distribution label or a grayscale label of emotions in the classification model, which can enhance the one-hot label with additional information, such as the intensity of other emotions and the correlation between emotions. Such an approach has been proven effective in alleviating the overfitting problem and improving the model robustness by introducing a distribution learning component in the objective function. However, the effect of distribution learning cannot be fully unfolded as it can reduce the model's discriminative ability within similar emotion categories. For example, "Sad" and "Fear" are both negative emotions. To address such a problem, we proposed a novel emotion extension scheme in the prior work (Li, Chen, Xie, Li, and Tao, 2021). The prior work incorporated fine-grained emotion concepts to build an extended label space, where a mapping function between coarse-grained emotion categories and fine-grained emotion concepts was identified. For example, sentences labeled "Joy" can convey various emotions such as enjoy, free, and leisure . The model can further benefit from the extended space by extracting dependency within fine-grained emotions when yielding predictions in the original label space. The prior work has shown that it is more apt to apply distribution learning in the extended label space than in the original space. A novel sparse connection method, i.e., Leaky Dropout, is proposed in this paper to refine the dependency-extraction step, which further improves the classification performance. In addition to the multiclass emotion classification task, we extensively experimented on sentiment analysis and multilabel emotion prediction tasks to investigate the effectiveness and generality of the label extension schema. Highlights: Identify the association between emotion categories and fine-grained emotion concepts. Suggest a novel emotion label extension schema. Device a classification framework incorporating distribution learning. Device a novel sparse connection mechanism, Leaky Dropout.